Vacinação e a apropriação do conhecimento imunológico por alunos do ensino médio: uma abordagem em pesquisa-ação - Sarah Eliane de Matos Silva (2019)
Vaccine is a suspension of organisms, or fraction of organisms, used to induce immunity and, consequently, reduce the spread of infections and occurrence of epidemics. Although the importance of vaccination in controlling infectious diseases is well established, several studies have shown that vaccination coverage in teenagers is low, mainly due to the lack of knowledge about the vaccines and the diseases they protect against. In addition, the vulnerability and inappropriate behavior of indifference to their health raise the risk of exposure of teenagers to infectious diseases. In this context, the present work, carried out with high school students from a state public school in the city of Betim-MG, was developed through the application of a didactic sequence, based on the methodology of action research, in order to promote health education in the school environment, improving knowledge and stimulating reflections in the context of scientific education. After carrying out the proposed activities, it was possible to verify the effectiveness of the methodology used for the acquisition of knowledge by students , besides promoting a greater interest and motivation than the traditional classes. In addition, it made it possible to explore the less understood issues more effectively and stimulated students' autonomy associated to the construction of their own knowledge.